1992
DOI: 10.1073/pnas.89.5.1842
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning and functional expression of the Schistosoma mansoni protective antigen triose-phosphate isomerase.

Abstract: M.1 monoclonal antibody has previously been shown to passively transfer partial resistance to schistosome infection within mice and to recognize a 28-kDa antigen that has peptide sequence homology with triose-phosphate isomerase (TPI; D-glyceraldehyde-3-phosphate ketol-isomerase, EC 5.3.1.1). We have now isolated the complete coding DNA for Schistosoma mansoni TPI and confirmed that this cDNA encodes the 28-kDa antigen recognized by M.1. The predicted translation product has strong homology with other TPIs, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…However, 21 of the 66 identified RV-reduced/disappearing protein spots (Table II), such as ␤-1,4-xylanase, pollen allergens, ␤-expansin, polygalacturonase, profilin A, enolase, and ascorbate peroxidase, have been detected in coat/wall-associated and pollen-released protein fractions of mature rice (14) and maize pollen (20). Further analyses revealed that 1) most of the identified RVreduced/disappearing proteins, such as members of the class III peroxidase family, polygalacturonase, and disulfide isomerase, have a potential extracellular targeting signal peptide in their N termini (Table II), and 2) 24 have been documented to be secreted/released extracellular proteins and/or cell surface/wall-associated proteins in other organisms, for example 2,3-bisphosphoglycerate-independent phosphoglycerate mutase (26), fructose-1,6-bisphosphate aldolase (27), and triose-phosphate isomerase (28). Thus, we propose that 51 of the 66 RV-reduced/disappearing identities (39 Unipros) were probably released, and the other 15 (14 Unipros) may really be down-regulated (Table II).…”
Section: And E)mentioning
confidence: 99%
“…However, 21 of the 66 identified RV-reduced/disappearing protein spots (Table II), such as ␤-1,4-xylanase, pollen allergens, ␤-expansin, polygalacturonase, profilin A, enolase, and ascorbate peroxidase, have been detected in coat/wall-associated and pollen-released protein fractions of mature rice (14) and maize pollen (20). Further analyses revealed that 1) most of the identified RVreduced/disappearing proteins, such as members of the class III peroxidase family, polygalacturonase, and disulfide isomerase, have a potential extracellular targeting signal peptide in their N termini (Table II), and 2) 24 have been documented to be secreted/released extracellular proteins and/or cell surface/wall-associated proteins in other organisms, for example 2,3-bisphosphoglycerate-independent phosphoglycerate mutase (26), fructose-1,6-bisphosphate aldolase (27), and triose-phosphate isomerase (28). Thus, we propose that 51 of the 66 RV-reduced/disappearing identities (39 Unipros) were probably released, and the other 15 (14 Unipros) may really be down-regulated (Table II).…”
Section: And E)mentioning
confidence: 99%
“…Extensive work has been carried out to identify schistosome molecules that confer partial but significant protection in different animal models. These include the Schistosoma mansoni 28-kDa and the S. japonicum 26-kDa glutathione S-transferase (GST) (5,32), the S. mansoni and S. japonicum 97-kDa paramyosin (13,25), the S. mansoni 28-kDa triose phosphate isomerase (29), the S. mansoni 23-kDa integral membrane antigen (24), and so forth. These vaccine candidates were selected by the World Health Organization for a series of independent trials to test their protective efficacy in laboratory animals (2).…”
mentioning
confidence: 99%
“…Both high levels of specific immunoglobulin E (IgE) in sera and gamma interferon (IFN-␥) in antigen-stimulated peripheral blood mononuclear cell (PBMC) cultures were associated with resistance to reinfection (1,22,24,25,27,28,56,57). These data suggest the participation of immunological mechanisms in human resistance to Schistosoma mansoni infection, with mixed cellular and humoral responses.Several S. mansoni antigens have been identified and tested in experimental models, with the induction of variable levels of protection against infection (11,32,49,59,61,(68)(69)(70)74). The World Health Organization (WHO) has selected six of these antigens for further in vitro studies with PBMC from subjects in areas of endemicity for schistosomiasis.…”
mentioning
confidence: 99%
“…Several S. mansoni antigens have been identified and tested in experimental models, with the induction of variable levels of protection against infection (11,32,49,59,61,(68)(69)(70)74). The World Health Organization (WHO) has selected six of these antigens for further in vitro studies with PBMC from subjects in areas of endemicity for schistosomiasis.…”
mentioning
confidence: 99%